INDOGLISH AS A SOCIOLINGUISTIC PHENOMENON: A CASE STUDY AT ENGLISH DEPARTMENTS UMMY SOLOK - Fitri Handayani; Mike Amelia (English Language Education Department, Universitas Majalengka, 2022)
This study looked into the use of Indoglish as a Sociolinguistic Phenomenon by English Department students of UMMY Solok. The indoglish utterances were collected using a descriptive qualitative approach in this study. The participants in this study were all English Department students in UMMY Solok's sociolinguistic class. The data for this study are snippets of speech gathered from the use of language in the sphere of daily education of students in the campus setting as a whole over the course of three months. Direct speech in everyday communication, which is supposed to contain the forms of 'Indoglish' is used to observe closely. Speech inducements are also used to collect data for this study. This method can be enhanced by recording directly or indirectly, publically or secretly. The interview will then proceed to describe the causes that led to the creation of Indoglish used by students. The study's findings suggest that 53 English words were recognized as Indoglish expressions from students' non-academic conversation. The data indicates that the likelihood of using Indoglish at the word level is higher than the likelihood of using phrases, clauses, or sentences. Meanwhile, the findings of the investigation revealed that this occurrence was caused by a number of variables. The majority of students utilize Indoglish in their conversations to build closeness, relaxed friendliness, and intimacy with their interlocutors, according to the findings. Second, the speaker is having trouble locating the correct term in Indonesia. Finally, this phenomena arose as a result of students' desire to improve their English language skills by employing Indoglish in regular discourse.